PENGARUH PENGUMUMAN STOCK SPLIT TERHADAP LIKUIDITAS SAHAM DAN RETURN SAHAM (Studi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Shochihatuz Zainia Fauzi; . Suhadak; Raden Rustam Hidayat (Fakultas Ilmu Administrasi Universitas Brawijaya, 2016)
This study aims the influence of stock split announcement on stock liquidity and stock return for determining the differences on Trading Volume Activity and abnormal return before and after the announcement of stock split. The stock liquidity in this study can be known through the Trading Volume Activity, whereas the stock return can be known trough the abnormal return. A type of research used in this study is a quantitative approach by using event study. The criteria for sampling used is purposive sampling, in accordance with prefetermined criteria that there are 32 companies sample. The result showed that there is a market reaction around the announcement of a stock split. However, there is no significant differences Trading Volume Activity and abnormal return before and after the announcement of a stock split. With regard to the research result, there is a positive reaction around the stock split announcement. The result research showed that investors are less interested in the shares offered, that Trading Volume Activity does not increase, then there is no an increase in liquidity. Furthermore, investors cannot enjoy the abnormal return over the longer term. Keywords: Stock Split, Trading Volume Activity, Abnormal Return, Corporate Action ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh pengumuman stock split serta untuk mengetahui perbedaan likuiditas saham dan return saham sebelum dan sesudah pengumuman stock split. Likuiditas saham pada penelitian ini dapat diketahui melalui Trading Volume Activity, sedangkan return saham dapat diketahui melalui abnormal return. Jenis penelitian yang digunakan adalah kuantitatif dengan penelitian peristiwa (event study). Kriteria pengambilan sampel menggunakan purposive sampling, sesuai dengan kriteria yang telah ditentukan terdapat 32 perusahaan sampel penelitian. Hasil analisis menunjukkan terdapat pengaruh pengumuman stock split. Akan tetapi tidak terdapat perbedaan signifikan Trading Volume Activity dan abnormal return sebelum dan sesudah pengumuman stock split. Berdasarkan hasil penelitian, terdapat reaksi positif di sekitar pengumuman stock split. Hasil penelitian menunjukkan investor kurang berminat terhadap saham yang ditawarkan sehingga trading volume activity tidak meningkat maka tidak terdapat peningkatan likuiditas. Selain itu, investor tidak dapat menikmati abnormal return dalam jangka lama. Kata Kunci: Stock Split, Trading Volume Activity, Abnormal Return, Corporate Action